2018
DOI: 10.3389/fmicb.2018.00709
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Bacterial Community Diversity Within the Rhizosphere of Three Phylogenetically Related Perennial Shrub Plant Species Across Environmental Gradients

Abstract: Rhizosphere microbial communities are of great importance to mediate global biogeochemical cycles, plant growth, and fitness. Yet, the processes that drive their assembly remain unclear. The perennial shrubs Caragana spp., which is well known for their role in soil and water conservation, provides an ideal system to study the biogeography of rhizosphere microorganism communities within natural ecosystems. In order to detect how bacterial rhizosphere communities vary in terms of community diversity and composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…These findings reflect the sensibility of soil fungi to changing climatic and edaphic conditions (Tedersoo et al, 2014). In contrast, rhizospheric bacterial communities had 44% of the OTUs in common, in disagreement other studies, which state that geographical distances reduce the similarity of bacterial communities (Martiny et al, 2011;Wang et al, 2017;Na et al, 2018). However, our results agree with those of Van der Walt et al (2016) from the Namib Desert, suggesting that there may be "similar underlying drivers" for microbial distribution in both west coast deserts.…”
Section: Microbiome Dynamics Along the Latitudinal Gradientsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings reflect the sensibility of soil fungi to changing climatic and edaphic conditions (Tedersoo et al, 2014). In contrast, rhizospheric bacterial communities had 44% of the OTUs in common, in disagreement other studies, which state that geographical distances reduce the similarity of bacterial communities (Martiny et al, 2011;Wang et al, 2017;Na et al, 2018). However, our results agree with those of Van der Walt et al (2016) from the Namib Desert, suggesting that there may be "similar underlying drivers" for microbial distribution in both west coast deserts.…”
Section: Microbiome Dynamics Along the Latitudinal Gradientsupporting
confidence: 89%
“…A cause for the minor size of the core microbiome are probably the divergent habitat conditions (soil physicochemical and environmental factors) along the latitudinal gradient (Nuccio et al, 2016;Na et al, 2018).…”
Section: Microbiome Dynamics Along the Latitudinal Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…Black circles reflect means for all pairwise comparisons within each of the eight soil types, for all combinations of two out of eight soil types (n = 28), within the six plant species, and for all combinations of two out of six plant species (n = 15) p values were determined through t-tests the developmental stage and physiological status of the host plant and thereby the composition of root exudates. Alternatively, specific soil physicochemical conditions may directly select for particular bacterial species in the rhizosphere [39]. When the quantitative contribution of all variables covered by the present study (Tables S2 and S3) to differences in the rhizobiome composition was assessed by variance partitioning, soil characteristics alone were found to explain most of the variance (30%).…”
Section: Potential Drivers Of the Variation In Grassland Rhizobiomesmentioning
confidence: 82%
“…In an effort to inspect the factors influencing rhizosphere bacterial community, Na et al (2018) investigated the rhizosphere bacterial community of the widely distributed perennial shrub Caragana in the arid and semi-arid areas of north China. The authors revealed the bacterial communities dominating the rhizosphere across three Caragana species belonged to Proteobacteria, Actinobacteria, Firmicutes, Bacteroidetes, Acidobacteria, Gemmatimonadetes, and Cyanobacteria, while on the genus level Pseudomonas, Acinetobacter, Bacillus, Stenotrophomonas, Burkholderia, Paenibacillus, Sphingobacterium, Chitinophaga, Arthrobacter, and Chryseobacterium were the most dominant genera.…”
Section: Bacterial Diversity and Factors Shaping The Bacterial Communmentioning
confidence: 99%